2017
DOI: 10.12693/aphyspola.131.678
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Thermal and Magnetic Properties of Amorphous Ribbons of Fe_{61}Co_{10}B_{20}Y_8Me_1 (where Me~=~W, Zr, Nb, Mo)

Abstract: This paper presents the results pertaining to thermal and magnetic studies of rapidly-cooled samples of the alloy family Fe61Co10B20Y8Me1 (where Me = Nb, Zr, W, Mo). The resulting ribbons, or tapes, have amorphous structure. It has been found that the addition of Me elements alters the thermal and magnetic properties. It is noted that the saturation magnetization decreases with increasing number of unpaired electrons on the valence shells. In addition, the value of the coercivity and effective anisotropy have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, the sample of the Fe 62 Co 9 W 1 Y 8 B 20 alloy (Figure 3b), which was made under the same conditions, shows the presence of a small number of grains of the Fe 5 Y and αFe crystalline phases. After the isothermal annealing process, conducted at a temperature close to the crystallization temperature [31] of the alloy for 10 min, the X-ray diffraction patterns for all of the samples revealed sharp, relatively narrow, peaks, indicating the presence of crystalline phases. In the sample of the Fe 61 Co 10 W 1 Y 8 B 20 alloy (Figure 3d) and the Fe 63 Co 8 W 1 Y 8 B 20 alloy (Figure 3f), the presence of two crystalline phases was detected: αFe and Fe 5 Y.…”
Section: Resultsmentioning
confidence: 99%
“…However, the sample of the Fe 62 Co 9 W 1 Y 8 B 20 alloy (Figure 3b), which was made under the same conditions, shows the presence of a small number of grains of the Fe 5 Y and αFe crystalline phases. After the isothermal annealing process, conducted at a temperature close to the crystallization temperature [31] of the alloy for 10 min, the X-ray diffraction patterns for all of the samples revealed sharp, relatively narrow, peaks, indicating the presence of crystalline phases. In the sample of the Fe 61 Co 10 W 1 Y 8 B 20 alloy (Figure 3d) and the Fe 63 Co 8 W 1 Y 8 B 20 alloy (Figure 3f), the presence of two crystalline phases was detected: αFe and Fe 5 Y.…”
Section: Resultsmentioning
confidence: 99%
“…No relationship was observed between the Co and Fe content and the coercive field value. Numerous studies of co-authors have shown that elements such as Zr, Mo, W, or Nb [23,24] have a significant impact on the reduction of H C in alloys based on Fe and Co. In addition, the authors observed a relationship between the value of the coercive field and the width of the amorphous halo.…”
Section: Discussionmentioning
confidence: 97%
“…Amorphous materials have been extensively studied for over half a century [1][2][3][4][5][6][7][8].The reason for interest in this group of materials are their unique properties, which are significantly better than for their crystalline counterparts with the same chemical compositions [9][10][11]. Amorphous materials divided into two groups: classic and massive [12][13][14][15][16].…”
mentioning
confidence: 99%